2012
DOI: 10.1007/s00192-012-1797-9
|View full text |Cite
|
Sign up to set email alerts
|

Low back pain does not improve with surgical treatment of pelvic organ prolapse

Abstract: Our study found a statistically significant but not clinically significant improvement of LBP after surgical repair of prolapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
2
1
Order By: Relevance
“…We also found that women with symptoms of POP were more likely to report PGP and/or LBP. This finding is contrary to what two previous studies have reported (238,239). The difference in findings might be due to differences in populations and measurements.…”
Section: Prevalence and Severity Of Pelvic Girdle Pain And/or Low Baccontrasting
confidence: 99%
“…We also found that women with symptoms of POP were more likely to report PGP and/or LBP. This finding is contrary to what two previous studies have reported (238,239). The difference in findings might be due to differences in populations and measurements.…”
Section: Prevalence and Severity Of Pelvic Girdle Pain And/or Low Baccontrasting
confidence: 99%
“…The numbers observed in our study thus correspond to those found in the literature, with a 38-51% occurrence of chronic pain, depending on whether a suture or tacker fixation was used. The association between genital prolapse and chronic pelvic and lumbar pain remains highly controversial [15][16][17][18][19][20][21][22][23][24]. One may wonder why LS using tackers should carry a greater risk of causing lumbosciatica than LS using a suture.…”
Section: Commentsmentioning
confidence: 99%
“…According to an FDA report, we are just beginning to see a small part of the iceberg of far more serious mesh complications . Should POP be dominated by the use of mesh?…”
Section: Introductionmentioning
confidence: 99%